Expanded vacuum-stable gels for multiplexed high-resolution spatial histopathology - Yunhao Bai; Bokai Zhu; John-Paul Oliveria; Bryan J. Cannon; Dorien Feyaerts; Marc Bosse; Kausalia Vijayaragavan; Noah F. Greenwald; Darci Phillips; Christian M. Schürch; Samuel M. Naik; Edward A. Ganio; et al. (Nature Communications, 2023)
Abstract Cellular organization and functions encompass multiple scales in vivo. Emerging high-plex imaging technologies are limited in resolving subcellular biomolecular features. Expansion Microscopy (ExM) and related techniques physically expand samples for enhanced spatial resolution, but are challenging to be combined with high-plex imaging technologies to enable integrative multiscaled tissue biology insights. Here, we introduce Expand and comPRESS hydrOgels (ExPRESSO), an ExM framework that allows high-plex protein staining, physical expansion, and removal of water, while retaining the lateral tissue expansion. We demonstrate ExPRESSO imaging of archival clinical tissue samples on Multiplexed Ion Beam Imaging and Imaging Mass Cytometry platforms, with detection capabilities of > 40 markers. Application of ExPRESSO on archival human lymphoid and brain tissues resolved tissue architecture at the subcellular level, particularly that of the blood-brain barrier. ExPRESSO hence provides a platform for extending the analysis compatibility of hydrogel-expanded biospecimens to mass spectrometry, with minimal modifications to protocols and instrumentation.